1995
DOI: 10.1002/cne.903610202
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of interactions between regenerating adult rat thalamic axons and Schwann cells in peripheral nerve grafts I. Neural cell adhesion molecules

Abstract: To gain insight into the possible molecular mechanisms underlying axonal regeneration of neurons of the adult central nervous system (CNS), we have investigated, by in situ hybridization and by immunocytochemistry, the localization and sites of synthesis of the neurite outgrowth-promoting cell surface molecules L1, N-CAM and its highly sialylated form, N-CAM-PSA, in and around peripheral nerve grafts implanted into the thalamus of adult rats. Normal unoperated adult rat thalamus contains N-CAM and L1 but no N-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
6

Year Published

1996
1996
2005
2005

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 56 publications
2
58
0
6
Order By: Relevance
“…2 B). Although it is impossible to determine the source of the PSA via light microscopy, previous studies that used electron microscopy have shown that the vast majority of PSA reexpressed in regener-ating nerves is neural in origin (Zhang et al, 1995). Consequently, the dramatic upregulation of PSA in the muscle and cutaneous pathways most likely is attributable to the reexpression of PSA by regenerating axons and not to the synthesis of PSA by neighboring Schwann cells.…”
Section: Psa Is Upregulated Differentially On Nerves Reinnervating Mumentioning
confidence: 99%
See 1 more Smart Citation
“…2 B). Although it is impossible to determine the source of the PSA via light microscopy, previous studies that used electron microscopy have shown that the vast majority of PSA reexpressed in regener-ating nerves is neural in origin (Zhang et al, 1995). Consequently, the dramatic upregulation of PSA in the muscle and cutaneous pathways most likely is attributable to the reexpression of PSA by regenerating axons and not to the synthesis of PSA by neighboring Schwann cells.…”
Section: Psa Is Upregulated Differentially On Nerves Reinnervating Mumentioning
confidence: 99%
“…However, there are several lines of evidence to suggest that the neural cell adhesion molecule (NCAM) and its polysialic acid (PSA) moiety are involved. PSA and NCAM are both reexpressed by regenerating motor axons after peripheral nerve in-jury (Zhang et al, 1995;Rutishauser and Landmesser, 1996). During development motor axons must express PSA to innervate their appropriate muscle target(s) selectively (Tang et al, 1992(Tang et al, , 1994.…”
Section: Introductionmentioning
confidence: 99%
“…Laminin in its synthesis and its distribution therefore may be one of the factors that play a role in the lack of inhibition of neurite outgrowth after antisense treatment. Alternatively, one cannot exclude that, rather than an alteration-or a lack thereof-in the synthesis of secreted molecules, the maintained ability of reactive astrocytes to support axonal regrowth may be related to membrane-bound molecules involved in cell-to-cell contact between neurons and astrocytes, such as cell adhesion molecules (for review, see Zhang et al, 1995).…”
Section: Inhibition Of Hypertrophy Induces Functional Changes In Astrmentioning
confidence: 99%
“…During peripheral nerve regeneration, L1 is expressed in motor neurons and Schwann cells (Martini and Schachner, 1988;Zhang et al, 2000). In the mammalian CNS, expression of L1 is increased in subpopulations of axotomized neurons only when their axons regrow into a permissive peripheral nerve graft (Zhang et al, 1995). Infusion of L1-Fc fusion protein into the lesioned adult rat spinal cord promotes locomotor recovery (Roonprapunt et al, 2003).…”
Section: Introductionmentioning
confidence: 99%